2011
DOI: 10.1167/11.12.18
|View full text |Cite
|
Sign up to set email alerts
|

When more is less: Extraction of summary statistics benefits from larger sets

Abstract: Despite several processing limitations that have been identified in the visual system, research shows that statistical information about a set of objects could be perceived as accurately as the information about a single object. It has been suggested that extraction of summary statistics represents a different mode of visual processing, which employs a parallel mechanism free of capacity limitations. Here, we demonstrate, using reaction time measures, that increasing the number of stimuli in the set results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 30 publications
8
113
3
1
Order By: Relevance
“…Our results combined with results from similar manipulations with ensembles of different size elements (Utochkin & Tiurina, 2014) suggest that Marchant et al's finding may have been an artifact of the conflation of number of elements and number of unique sizes in their ensembles. It should be noted that there was no evidence for the improvement in performance, or reduction in RT, associated with having more elements as previously reported for ensembles of different size elements (Robitaille & Harris, 2011). Whether this is a result of a difference in the ensemble processing of these types of stimuli or some experimental factor is an area for further research.…”
Section: Exhaustive Processing Versus Subsamplingmentioning
confidence: 65%
See 1 more Smart Citation
“…Our results combined with results from similar manipulations with ensembles of different size elements (Utochkin & Tiurina, 2014) suggest that Marchant et al's finding may have been an artifact of the conflation of number of elements and number of unique sizes in their ensembles. It should be noted that there was no evidence for the improvement in performance, or reduction in RT, associated with having more elements as previously reported for ensembles of different size elements (Robitaille & Harris, 2011). Whether this is a result of a difference in the ensemble processing of these types of stimuli or some experimental factor is an area for further research.…”
Section: Exhaustive Processing Versus Subsamplingmentioning
confidence: 65%
“…Although the observed insensitivity to number of elements lends weight to holistic processing explanations (e.g., Robitaille & Harris, 2011), a subsampling process immune to increasing elements is still possible. For example, attention might be distributed across all elements, but only a subsample is included when encoding summary statistics (see also Utochkin & Tiurina, 2014, p. 17).…”
Section: Exhaustive Processing Versus Subsamplingmentioning
confidence: 95%
“…We further found that there is no impact of increasing the number of elements in an ensemble -observers were able to identify the mean equally reliably whether required to average 4, 8 or 16 patches of color [13]. The robustness of mean identification ability to changes in number of elements has also been demonstrated for ensemble perception of size [e.g., 2,18,[27][28][29] and faces [12,30], and is suggestive of an efficient mechanism where processing occurs in parallel, across the whole display and all items [17].…”
Section: Introductionmentioning
confidence: 62%
“…Response variability was higher with static form information as compared with dynamic form information ip < .01; Figure 3C). We performed a separate analysis to determine if perception of a crowd's heading was dependent on a particular stage of the gait cycle (e.g., response variability could have been lowest on trials where walkers had extended ankles; Chang & Troje, 2009;Mather et al, 1992;Rosenholtz, 1999;Thurman & Grossman, 2008;Troje & Westhoff, 2006). No clear pattern emerged across observers, suggesting that any use of a particular stage of the gait cycle, if at all, was idiosyncratic or irrelevant.…”
Section: Upright-coherent Crowdsmentioning
confidence: 99%